Studies on the Pinctada fucata BMP-2 Gene: Structural Similarity and Functional Conservation of Its Osteogenic Potential within the Animal Kingdom - Takami, Akiko; Kato, Hirotaka; Takagi, Ryousuke; Miyashita, Tomoyuki (International Journal of Zoology, 2013)
Bone morphogenetic protein (BMP)-2 plays an important role in morphogenesis in both vertebrates and invertebrates. BMP-2 is one of the most powerful bioactive substances known to induce the osteogenic differentiation of mesenchymal cells. We examined the structural and functional conservation of Pinctada fucata BMP-2 in inducing osteogenesis in the murine mesenchymal stem cells, C3H10T1/2. Exposure of C3H10T1/2 cells to the recombinant mature fragment of Pinctada fucata BMP-2 resulted in osteoblastic differentiation. The sequence, SVPKPCCVPTELSSL, within the C-terminal portion of Pinctada fucata BMP-2, is homologous to the knuckle epitope of human BMP-2. This synthetic polypeptide was able to induce differentiation of C3H10T1/2 along the osteoblastic lineage, as confirmed by an increase in alkaline phosphatase activity, and the accumulation of calcium, as determined by von Kossa staining. Furthermore, using immunohistochemical staining, we observed an increased expression of collagen type I, osteopontin, and osteocalcin, which are known markers of osteogenesis. These results show that BMP-2 is conserved, not only in terms of its homology at the amino acid sequence, but also in terms of driving the formation of hard tissues in vertebrates and invertebrates.